The relationship between intuitive eating and body image is moderated by measured body mass index. (April 2019) - Keirns, Natalie G.; Hawkins, Misty A.W.
Abstract: Intuitive eating (IE) is a pattern of adaptive eating that has been associated with positive psychosocial and physical factors (e.g., positive body image, lower body mass index; BMI). However, BMI has also been negatively associated with body image. Our goal was to evaluate whether IE is uniquely associated with body image, independent of objective weight status (measured BMI). Further, as a secondary aim, this study analyzed potential moderators (BMI, sex, race-ethnicity) in the IE-body image relationship. Data from 136 adults (34 ± 15 years old, 74% female, 56% Caucasian) were analyzed. BMI was objectively measured in-lab. IE was measured with the Intuitive Eating Scale-2. Body image was measured as a Body Concern composite created using the Eating Disorder Examination-Questionnaire (EDE-Q 6.0) Weight and Shape Concern subscales. Demographic factors and covariates were measured via self-report. Regressions revealed that, after controlling for BMI and covariates, Total IE was uniquely associated with Body Concern ( β = −0.463, p < .001), as were two of the IE subscales: Unconditional Permission to Eat (Unconditional Permission; β = −0.320, p < .001) and Eating for Physical Rather than Emotional Reasons (Physical Reasons; β = −0.408, p < .001). BMI was also found to be a significant moderator between IE and Body Concern for Total IE ( b = 0.071, p = .017), Unconditional Permission ( b = 0.067, p = .001), and Physical Reasons ( b = 0.038, p = .021), with the negative association between IE and Body Concern being strongest for healthy weight individuals. Greater IE was associated with lower body image concern across the weight spectrum, though this relationship was strongest for healthy weight individuals and attenuated as BMI increased. Highlights: Intuitive eating (IE) was associated with less negative body image, adjusting for measured BMI. Unconditional Permission & Physical Reasons were the most important facets in this relationship. The IE-body image relationship was strongest at healthy weight and decreased with increasing BMI.